HUMAN RESOURCE MANAGEMENT STRATEGIES IN THE DEVELOPMENT OF EDUCATIONAL ENTREPRENEURSHIP AT MUHAMMADIYAH 3 PANDAAN ELEMENTARY SCHOOL - Rakhma, Rakhmatusakdiyah; Rindanigsih, Ida (Antis Publisher, 2024)
The purpose of this study was to determine the challenges faced in developing educational entrepreneurship at SD Muhammadiyah 3 Pandaan and to find out the strategies used to align human resources (HR) with the vision and mission of SD Muhammadiyah 3 Pandaan. This type of research uses a descriptive qualitative approach and data collection interviews, observation. The research location is SD Muhammadiyah 3 Pandaan. The results of the study stated that SD Muhammadiyah 3 Pandaan took strategic steps in the development of the industrial revolution 4.0 by developing entrepreneurship in the field of education, namely TPQ Madin, but challenges arose such as human resource management at TPQ Madin Al Jauharah which had not run in harmony with SD Muhammadiyah 3 Pandaan and the school responded by carrying out effective strategies. The positive impact is not only limited to TPQ Madin but also felt by the school, and the existence of TPQ Madin creates new jobs for the surrounding youth.